Interference of the Zika Virus E-Protein With the Membrane Attack Complex of the Complement System - Malekshahi, Zahra; Schiela, Britta; Bernklau, Sarah; Banki, Zoltan; Würzner, Reinhard; Stoiber, Heribert (Frontiers in Immunology, 2020)
The complement system has developed different strategies to clear infections by several effector mechanisms, such as opsonization, which supports phagocytosis, attracting immune cells by C3 and C5 cleavage products, or direct killing of pathogens by the formation of the membrane attack complex (MAC). As the Zika virus (ZIKV) activates the classical complement pathway and thus has to avoid clearance by the complement system, we analyzed putative viral escape mechanisms, which limit virolysis. We identified binding of the recombinant viral envelope E protein to components of the terminal pathway complement (C5b6, C7, C8, and C9) by ELISA. Western blot analyses revealed that ZIKV E protein interfered with the polymerization of C9, induced on cellular surfaces, either by purified terminal complement proteins or by normal human serum (NHS) as a source of the complement. Further, the hemolytic activity of NHS was significantly reduced in the presence of the recombinant E protein or entire viral particles. This data indicates that ZIKV reduces MAC formation and complement-mediated lysis by binding terminal complement proteins to the viral E protein.